2002
DOI: 10.1038/sj.leu.2402352
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and biological implications of partial tandem duplication of the MLL gene in acute myeloid leukemia without chromosomal abnormalities at 11q23

Abstract: The clinical and biological features of acute myeloid leukemia (AML) with 11q23/MLL translocations are well known, but the characteristics of AML with partial tandem duplication of the MLL gene have not been explored comprehensively. In this study, MLL duplication was analyzed, in 81 AML patients without chromosomal abnormalities at 11q23, using Southern blotting, genomic DNA polymerase chain reaction (PCR), reversetranscription PCR and complementary DNA sequencing. Nine patients showed partial tandem duplicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 24 publications
2
59
0
Order By: Relevance
“…AML with trisomy 11 has been shown to have a high frequency of MLL PTD [22][23][24] and interestingly, this MLL PTD likely occurs in the extra copy of chromosome 11. 25 Although the hypothesis that MLL PTD is leukemogenic has been challenged by its ubiquitous existence in healthy individuals and their life-long persistence, 26 recent observations and animal models have shown that MLL PTD disturbs normal hematopoiesis in a gain-of-function manner, as well as DNA hypermethylation and epigenetic silencing of the tumor suppressor gene.…”
Section: Discussionmentioning
confidence: 99%
“…AML with trisomy 11 has been shown to have a high frequency of MLL PTD [22][23][24] and interestingly, this MLL PTD likely occurs in the extra copy of chromosome 11. 25 Although the hypothesis that MLL PTD is leukemogenic has been challenged by its ubiquitous existence in healthy individuals and their life-long persistence, 26 recent observations and animal models have shown that MLL PTD disturbs normal hematopoiesis in a gain-of-function manner, as well as DNA hypermethylation and epigenetic silencing of the tumor suppressor gene.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to the frequency of MLL-PTD, which is equally low in pediatric AML, ranging from 1 to 10% depending on the screening method, 13,[37][38][39] as well as in adult AML, in the range of 5-10%. 37,[40][41][42][43][44][45][46][47] The different translocation partners of the rearranged MLL gene So far, more than 60 different fusion partners of MLL have been identified. Approximately 50% of pediatric AML cases with an MLL rearrangement consist of t(9;11)(p22;q23).…”
Section: Epidemiology Of Mll Aberrations In Pediatric Amlmentioning
confidence: 99%
“…Mutation analyses were performed on CEBPA in the only exon, 20 WT1 in exons 7, 8 and 9, 21 MLL-PTD that spanned exons 2-8, 22 JAK2 on V617F hot spot, 23 PTPN11 in exons 3 and 13, 24 RUNX1 in exons 3-8, 25 c-KIT in exons 8, 10, 11, 12 and 17, 26 RAS on codons 12 and 13, and 61 in exons 1 and 2, 27 FLT3-TKD on codon D835, 28 IDH1 on R132 hotspot, 14 ASXL1 in exon 12, 29 NPM1 on hotspot involving the C terminal portion of the transcript with a four nucleotides insertion between positions 960 and 961, 30 and FLT3-ITD in exon 14 31 as described previously. Mutations were detected by direct sequencing on the PCR products, and the sensitivity of each assay was about 15%.…”
Section: Mutation Analysismentioning
confidence: 99%